2022
DOI: 10.3389/fpsyg.2022.874895
|View full text |Cite
|
Sign up to set email alerts
|

How Does Career Calling Influence Preservice Teachers' Learning Engagement? A Multiple Mediating Roles of Occupational Self-Efficacy and Vocational Outcome Expectation

Abstract: This study used social cognitive career theory (SCCT) to explore the relationships between career calling, occupational self-efficacy, vocational outcome expectation, and learning engagement among preservice teachers at a normal university in China. Data from 1,029 preservice teachers were analyzed using Structural Equation Modeling. The results revealed that career calling was found to be significantly and positively affected on learning engagement; occupational self-efficacy and vocational outcome expectatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
2
2
0
Order By: Relevance
“…Nursing undergraduates with higher CSE and CC scores have higher levels of study engagement than students from all four grades. The findings of this research are consistent with previous studies, such as Tims and Akkermans (2017) showed individuals with higher CSE have higher levels of learning engagement and Shang revealed that career calling was found to be significantly and positively affected learning engagement (Shang et al, 2022). Interestingly, in this study, we found that CSE still had a significant positive effect on study engagement, but the influence coefficient was smaller than before adding CC as a mediator.…”
Section: Ta B L Esupporting
confidence: 91%
“…Nursing undergraduates with higher CSE and CC scores have higher levels of study engagement than students from all four grades. The findings of this research are consistent with previous studies, such as Tims and Akkermans (2017) showed individuals with higher CSE have higher levels of learning engagement and Shang revealed that career calling was found to be significantly and positively affected learning engagement (Shang et al, 2022). Interestingly, in this study, we found that CSE still had a significant positive effect on study engagement, but the influence coefficient was smaller than before adding CC as a mediator.…”
Section: Ta B L Esupporting
confidence: 91%
“…Specifically, we hypothesized that career calling would directly or indirectly predict the learning engagement of vocational nursing students in the Chinese context through vocational commitment and career adaptability. Our results confirmed this hypothesis, which is consistent with previous studies on the relationship between career calling, learning outcomes and personal wellbeing ( Duffy et al, 2011a , 2014 ; Duffy and Dik, 2013 ; Shang et al, 2022 ). The findings also suggested that career calling is an important psychological resource for strengthening students’ motivation and engagement in learning.…”
Section: Discussionsupporting
confidence: 93%
“…Learning engagement was assessed using the Chinese version of the Utrecht Work Engagement Scale for Students ( Gan et al, 2007 ). The scale has previously been used to research Chinese educational contexts (e.g., Wu et al, 2020 ; Shang et al, 2022 ; Wang et al, 2022 ). It consists of 17 items and 3 dimensions: vigor, dedication, and absorption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on prevocational education has found a significant positive relationship between career calling and readiness for prevocational learning (Hirschi & Herrmann, 2012). Individuals who exhibit a career calling may have higher expectations of their future success, thereby enhancing their level of engagement in academic pursuits during their university years (Shang et al, 2022). Empirical research has suggested that the career calling of preservice teachers positively predicts their learning engagement and that individuals with a stronger career calling are more engaged in learning (Chen et al, 2016).…”
Section: The Chain Mediating Effects Of Career Calling and Learning E...mentioning
confidence: 99%